Fine- and broad-scale distribution of a cushion plant species: Patterns and predictors for Euphorbia clavarioides. Issue 1 (1st January 2018) - Momberg, Mia; Greve, Michelle; van der Merwe, Stephni; le Roux, Peter C.
ABSTRACT: Cushion plants are a key Arctic, Antarctic, and alpine growth form, with many cushion-forming species strongly affecting community structure in abiotically stressful environments. Despite their ecological importance, there is little information about what drives the distribution of species exhibiting this growth form. This study investigates the determinants of the distribution of a cushion plant species, Euphorbia clavarioides at (1) a fine scale, using field-collected predictors from an alpine landscape; and (2) a broad scale, using distribution records and climate data across the species' distributional range. At the fine scale, the species was locally rare (occurring in about 4 percent of samples) and may be limited to specific microsites by interspecific competition with taller-growing species. Broad-scale species distribution modeling showed that both temperature and rainfall are important in predicting the distribution of E. clavarioides with a higher probability of occurrence in areas with higher annual precipitation and mean annual temperatures < 15°C. Given the species' sensitivity to competition and abiotic conditions (high temperatures and low precipitation), E. clavarioides may be vulnerable to environmental changes. Therefore, assuming that other cushion plant species exhibit similar patterns, species of this growth form may be particularly useful indicators of change in alpine, Arctic, and Antarctic areas.